WETU TELU; Suatu Bentuk Keberagaman Pendidikan Pembebasan Berbudaya Masyarakat Lombok - Saladin, Bustami (JURNAL KARSA (Terakreditasi No. 80/DIKTI/Kep/2012), 2012)
AbstractOn each occasion many cultural experts, observers of culture and cultural practitioners feel a great concern to the culture of the past who have started eroded by foreign cultures is not a country boy culture. Concerns can be seen from at least the younger generation who still recognize and remember the ancestors of its culture that are considered modern and outdated At this time the traditional culture which is a tradition of delivering the message has long been used long before humans knew the writing, community advocates maintain that tradition this ceremony as a tradition that has been "normal" or ordinary because from birth they have followed the custom. For example telu Wetu culture which is the liberation of cultural diversity and community education Lombok past. Telu Wetu Islam or Islamic Sasak in Lombok is a type of local Islam combined with traditional values. Islam is the sasak Wetu Telu who, despite claiming to be Muslims, continue to worship the spirits of the ancestors, the various gods and other spirits in their locality. This kind of Islam termarginalisasikan, get attack from Islam since the first Five Left now and even the future, the agricultural community there is a tendency still to carry its people and preserve ancestral traditions which has been running decades ago. Tradidi-traditions that still exist purely in accordance with its time, but some are already experiencing reductions and the addition of all of which are adjusted by age. Kata-kata kunciislam, budaya, wetu telu